Electronic and optical properties of defective MoSe2 repaired by halogen atoms from first-principles study - Yuefeng Guo; Yujin Ji; Huilong Dong; Lu Wang; Youyong Li (AIP Advances, 2019)
Using first-principles calculations, we have investigated the electronic and optical properties of MoSe2 with Se vacancies (SVSe, α-DVSe, and β-DVSe) and further repaired by halogen atoms (F, Cl, Br and I). For the MoSe2 with Se vacancies, Cl, Br and I atoms can occupy the Se vacancies and form three bonds with the neighboring Mo atoms, but F atom only can form two F-Mo bonds with the lowest adsorption energies due to its smaller atomic radius. Halogen atoms possess one more electron than Se atom, which results in a local magnetic moment of 1µB for single vacancy and 2µB for double vacancies. The MoSe2 with Se vacancies exhibits n-type doping semiconductor, which agrees well with the experimental observations. After halogen atoms doping in the defective site, the defective levels shift from electron donor levels to the electron acceptor levels, and finally reduces the n-type doping from the defective structure through a p-doping process. Compared to the defective MoSe2, absorption enhancement around low energy area of 0∼3 eV is observed in the halogen-repaired MoSe2 structures. Our results provide new insights in structural repairing of the transition metal dichalcogenides and promote their remarkable properties for applications in optoelectronics.